Synergistic Rewards for Proactive Behaviors: A Study on the Differentiated Incentive Mechanism for a New Generation of Knowledge Employees Using Mixed fsQCA and NCA Analysis - Jie Zhou; Junqing Yang; Bonoua Faye (Systems)
In practice, the new generation of knowledge-based employees often exhibits a “lying flat” attitude. This reflects the failure of organizational incentive mechanisms. In order to improve the incentive system and encourage employees to be proactive, the study explores and compares the synergistic effects of different rewards tools on various forms of proactive behavior in the new generation of knowledge employees. After conducting fsQCA and NCA analyses on paired data from 93 leaders and 210 employees based on the ERG theory, the findings indicate that no single reward tool is a necessary condition for triggering high proactive behavior. Instead, different reward tools need to work in synergy to produce effective motivation. Three patterns drive employees to exhibit high individual task proactivity. They are the “Dual-Drive Salary Security and Moderate Labor Dominant” pattern, the “Moderate Labor Dominant” pattern, and the “Salary Security Dominant” pattern. Two patterns drive employees to demonstrate high team member proactivity, namely the “Employee Care Dominant High-Investment” pattern and the “Pay Fairness Dominant High-Investment” pattern. Additionally, good work experience (i.e., colleague relationships) in the workplace has a significant impact on both types of proactive behavior. The research conclusions will provide insights and references for enterprise managers to design more targeted compensation incentive policies and unleash the vitality of the new generation of knowledgeable employees.